School characteristics and pupils’ thoughts of leaving upper secondary school: The INSchool project - Torland, Emilie Aas; Karlstad, Cecilie; Thørrisen, Mikkel Magnus; Bonsaksen, Tore; Haslerud, Sturla Inge; Aas, Randi Wågø (Frontiers in Psychology, 2024)
Introduction: Understanding pupils' thoughts about leaving school may contribute to better identify those at risk of dropping out. Thus, we explored the associations between perceived psychological demands, decision control, and social support from teacher and fellow pupils, and pupils' thoughts about leaving upper secondary school. Methods: Cross-sectional data from a convenience non-probability sample of 249 pupils from 12 Norwegian upper secondary schools were collected using a school-modified version of the work-focused Job Content Questionnaire (JCQ). Adjusted logistic regression was used to analyse the data.Results: Pupils who experienced higher psychological demands and lower social support from fellow pupils were more likely to experience thoughts of leaving school compared to those who experienced lower demands and high levels of social support. Decision control was not significantly associated with thoughts about leaving school. Conclusion: High psychological demands may increase the likelihood of considering leaving school. Peer support can lessen such thoughts. Implication: Identifying whether pupils are thinking about leaving school can help identify those who are at risk of dropping out of upper secondary school.